Keanekaragaman Gulma pada Pertanian Padi (Oryza sativa) Binaan Dinas Pangan Pertanian, Kelautan dan Perikanan Kota Langsa - Juli Trianda; Zulfan Arico; Jatu Purnawaty (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Weeds can cause losses slowly as long as they interact with plants. This practical work aims to find out what types of weeds are found in agricultural land assisted by the Department of Food, Agriculture, Maritime Affairs and Fisheries of Langsa City and the effect of weeds on rice cultivation. The method used in this research is field observation and quantitative (identification). The data obtained from the results of the determination of the frame is used to calculate the Weed Diversity Level by first determining the Diversity Index Value (Shannon Wienner). Observations were made in 3 villages, namely Cinta Raja Village, Sukarejo Village and Alue Pineung Village which are located in East Langsa District. There are 6 types of weeds found in Cinta Raja Village, in Sukarejo Village there are 8 types and Alue Pineung Village there are 5 types.